A few observations on the present position of the Irish national school teachers, as regards salaries, pensions, and residences - Ferguson, John (Statistical and Social Inquiry Society of Ireland, 1882)
On the 5th March, 1875, Mr. Charles Henry Meldon, M.P. for Kildare, delivered a speech in the House of Commons which contains most valuable information regarding the then position of the Irish National School teachers. The honourable and learned gentleman summarized the grievances of the teachers under three heads, viz.:?insufficient salaries, the great want throughout the entire country of residences, and the absence of any provision for teachers when overtaken by old age or infirmity. He showed that the average salary of teachers, male and female, did not exceed #45 per annum; and he then pertinently asked??What is this salary for men and women who spend their lives studying and teaching??
Read before the Society, 31 January 1882
Keywords: Teachers' conditions; Education; Teachers' salaries; Teachers' pensions; 314.15